The Role of Employee Engagement in Bridging the Relationship between Perceived Communication Satisfaction and Organizational Commitment - Diniawaty, Shintya Awalin; Prahiawan, Wawan; Kambara, Roni (PT Aksara Indo Rajawali, 2025)
This study examines employee engagement's function as a mediating variable in the correlation between perceived communication satisfaction and organizational commitment. The employed study method was a quantitative approach utilizing a survey design, with 84 state public servants participating as respondents. The data were examined utilizing Structural Equation Modeling (SEM). The findings indicated that perceived communication satisfaction significantly enhances employee engagement, but does not substantially affect organizational commitment. Research shows that employee engagement markedly enhances organizational commitment and mediates between perceived communication satisfaction and organizational commitment. This study's findings underscore the significance of employee engagement in connecting perceived communication satisfaction with organizational commitment. This study highlights the necessity of enhancing internal communication and employee engagement programs to bolster organizational commitment, hence facilitating the attainment of corporate objectives.